1935
DOI: 10.1002/path.1700410107
|View full text |Cite
|
Sign up to set email alerts
|

The paracolon group of bacteria

Abstract: IN the routine bacteriological examination of faxes in Egypt, one frequently encounters coliform organisms giving acid and gas in glucose and rnannite and no change in sucrose or lactose in 24-48 hours, yet not agglutinating with paratyphoid sera. Some workers have described similar organisms as inagglutinable paratyphoid, others as paracolon bacilli ; the latter t , e m is employed in this paper. Literature.Gilbert and Lion (1893) described a group of coliform organisms found in the stools of dysentery patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1940
1940
1951
1951

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Some correlation was found between fermentation and agglutination. Sandiford (1935) investigated 41 paracolon cultures isolated from dysenteric stools. All the strains produced acid and gas in glucose and nearly all formed indole.…”
Section: Antigenic Relationships In the Paracolon Groupmentioning
confidence: 99%
See 3 more Smart Citations
“…Some correlation was found between fermentation and agglutination. Sandiford (1935) investigated 41 paracolon cultures isolated from dysenteric stools. All the strains produced acid and gas in glucose and nearly all formed indole.…”
Section: Antigenic Relationships In the Paracolon Groupmentioning
confidence: 99%
“…The practice of assigning to the coliform group certain strains of organisms which fail to produce gas in lactose or in any other carbohydrate or do not ferment lactose, is not without precedent (Topley and Wilson (1937), Fothergill (1929), Sandiford (1935 and others). Stuart, Griffin and Baker (1938) found that several coliform strains isolated as anaerogenic, in the course of several months produced gas in lactose and that occasionally aerogenic cultures lost their ability to produce gas.…”
Section: Antigenic Relationships In the Paracolon Groupmentioning
confidence: 99%
See 2 more Smart Citations